PEMBELAJARAN PAI SEBAGAI MEDIA INTERNALISASI MODERASI BERAGAMA DALAM MEMBENTUK REGULASI EMOSI DAN PERILAKU SISWA KELAS 4 SDN 81 MALLUSESALO - Olivia Sudirna Putri Olivia; Ahmad Rizaldi; Hairul Amri; Fauzan; Ummul Mahirah NL; Besse Mutmainnah; Indo Santalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted to examine how Islamic Religious Education (PAI) learning can be a means of internalizing religious moderation, which will influence the emotional and behavioral control of fourth-grade students at SDN 81 Mallusesalo. The importance of religious moderation lies in its ability to foster an attitude of tolerance, balance, and respect for differences since children are in elementary school. In this study, the method used is a descriptive qualitative approach through observation, interviews, and documentation. The findings of this study indicate that the integration of religious moderation values ​​​​in PAI learning can have a significant impact, students are able to develop the ability to control emotions, demonstrate mutual respect, and build more positive behavior in daily interactions. In addition, teachers play a crucial role in designing contextual learning strategies that emphasize the practice of tolerance, justice, and togetherness. Therefore, PAI learning not only functions as a means of transferring religious knowledge, but also as a medium for character formation that aligns with the values ​​​​of religious moderation.